Solve using division algorithm and find GCD. 2x³+2x²-2x+2,6x³+12x²+6x+12
Answers
Answered by
3
Now p(x)÷ (x-1) = (2x²+3x+2) , remainder has to be zero, as divisor is a factor.
P(x) = ( x-1) (2x²+3x+2) ………….(1)
Similarly, q(x)= ( x-1)(3x²+x+2)……….(2)
Hence HCF= ( x-1)
P(x) = ( x-1) (2x²+3x+2) ………….(1)
Similarly, q(x)= ( x-1)(3x²+x+2)……….(2)
Hence HCF= ( x-1)
Similar questions
Math,
9 months ago
Social Sciences,
9 months ago
Math,
9 months ago
Math,
1 year ago
Geography,
1 year ago
Computer Science,
1 year ago